Sífilis gestacional e congênita: análise epidemiológica antes e após a implementação de uma política pública para o controle da sífilis congênita em Iguatu – Ceará/Brasil - Albuquerque, Fideralina Rodrigues de (2023)
Syphilis is considered a sexually transmitted infection that, when not treated early and adequately, can develop into a chronic illness. Faced with the problem of Syphilis, the municipality of Iguatu-CE was one of the two municipalities in Ceará benefiting from the “Projeto Carta Acordo OPAS” which aimed to reduce the incidence rate of congenital Syphilis. The municipality's participation promoted changes in the way of tackling the syphilis problem, in which a series of recommendations were adopted, constituting a municipal public policy. As objectives, we attempted to carry out an epidemiological analysis of cases of gestational and congenital syphilis in the municipality of Iguatu-CE from May 2019 to April 2023, emphasizing the repercussions that occurred after the implementation of public policy in the municipality. As method, as method, we got information from gestational and congenital syphilis notification forms, made available by the Notifiable Diseases Information System – SINAN, was used. The data were disaggregated into periods, the first being from May 2019 to April 2021 (closing date of the training provided by the Project and beginning of actions implemented by the municipality) and the second between May 2021 to April 2023. The epidemiological description was carried out based on global descriptive statistics, as well as comparative and correlation analyze between the two periods. 83 new cases were reported throughout the period, 71 cases of gestational syphilis and 12 of congenital syphilis. There was an increase in notifications of cases of gestational syphilis and a 50% reduction in cases of congenital syphilis after the public policy. The highest prevalence occurred in young, black and mixed-race women with low education. Clinically, an improvement in indicators is observed after the implementation of public policy, such as a greater proportion of diagnoses confirmed in the first trimester of pregnancy and a greater proportion of treatments carried out appropriately. Concluding, the reduction in underreporting of gestational syphilis and vertical transmission of syphilis are associated with the implemented municipal public policy. Thus, as the changes implemented by the Department of Health present a low cost for the municipality, it is recommended that this public policy be extended to other municipalities in the State of Ceará, encouraging actions such as improving the testing, monitoring and treatment processes offered in Basic Health Care, in addition to allowing the prescription and administration of Benzantine Penicillin to be carried out by trained nurses. As in other evidence, the cases of gestational and congenital syphilis in the municipality of Iguatu-CE point to problems of inequity in access to health, mainly affecting pregnant women in situations of social vulnerability, making it necessary to broaden the perspective and care in relation to women in this social extract.